Can E-Filing Reduce Tax Compliance Costs in Developing Countries? - Yilmaz, Fatih; Coolidge, Jacqueline (World Bank, Washington, DC, 2014)
The purpose of this study is to investigate the association between electronic filing (e-filing) and the total tax compliance costs incurred by small and medium size businesses in developing countries, based on survey data from South Africa, Ukraine, and Nepal. A priori, most observers expect that use of e-filing should reduce tax compliance costs, but this analysis suggests that the assumption should be more nuanced. In particular, policies that require business taxpayers to submit paper-based information in addition to their e-filing roughly negate savings that would otherwise be realized. In addition, adoption of e-filing requires an up-front investment by the business not only in capital assets, but also in the time, effort, and resources required to learn how to use e-filing properly and efficiently. Small businesses, in particular, are likely to face a steep "learning curve" and should probably not be forced to use e-filing before the majority of them have access to computers (with reliable electricity service) and have had a chance to become familiar with both computer use and the Internet.